0
$\begingroup$

I'm trying to solve this differential equation, here $y$ is a function with variable $x$:

$1 + y'^2 = yy''$

Here is my solution:

$$\left(\frac{y'}{y}\right)' = \left(\frac{y''y - y'^2}{y^2}\right) = \frac{1}{y^2}$$ Let $z = \frac{y'}{y}$. So from above equation, we have: $$z' = \frac {1}{y^2} \Rightarrow z = \frac{-1}{y} + C_1 \Rightarrow \frac{y'}{y} = \frac{-1}{y} + C_1 \Rightarrow y' = C_1y - 1$$ $$\Rightarrow \int\frac{dy}{C_1y - 1} = \int\frac{dx}{x} \Rightarrow \ln(C_1y - 1) = C_1x + C_2$$

This solution is different with the solution in my book, which is $y = C_1\cosh {x+C_1 \over C_2}$. So mysolution is wrong, but I can't find where the mistake is. Can anyone help me to point it out, and can we use my path to solve this equation? Thanks for taking your time

$\endgroup$
  • 1
    $\begingroup$ If you differentiate your expression for $z$ I get $\frac{y'}{y^2}$, which is not the same as $\frac{1}{y^2}$. $\endgroup$ – Kwin van der Veen Oct 28 '15 at 3:40
  • $\begingroup$ the equation $y'=C_1 y-1$, the solution is not logarithm. But it is also not $cosh$. I think it is $\frac{d}{d x}(\frac{y'}{y})=\frac{1}{y^2}=\frac{d}{dy}(\frac{-1}{y}+C_1)$ , so $\frac{y'}{y} \neq (\frac{-1}{y}+C_1)$ $\endgroup$ – Alexis Oct 28 '15 at 6:23
  • $\begingroup$ It does not seem that $y = c_1\cosh( {x+c_1 \over c_2})$ satisfies the differential equation. $\endgroup$ – Claude Leibovici Oct 28 '15 at 8:57
3
$\begingroup$

When you write $z'=1/y^2$, you are differentiating with respect to $x$. But then you integrate with respect to $y$.

The independent variable $x$ does not appear explicitly. Let $y'=p$ and consider $p$ as a function of $y$. Then $$ y''=\frac{dp}{dx}=\frac{dp}{dy}\,\frac{dy}{dx}=p\,\frac{dp}{dy}. $$ The equation becomes $$ 1+p^2=y\,p\,\frac{dp}{dy}\implies\frac{p\,dp}{1+p^2}=\frac{dy}{y}. $$ Integrating we get $$ \frac12\log(1+p^2)=\log y+C\implies p=y'=\pm\sqrt{C^2\,y^2-1}. $$ The solution is $$ \int\frac{dy}{\sqrt{C^2\,y^2-1}}\,dy=\pm x+K. $$

$\endgroup$
  • $\begingroup$ Oh, great. So I guessed the solution from my book(which is $y = C_1 \cosh{x + C_1 \over C_2}$ is wrong. Thanks a lot $\endgroup$ – le duc quang Oct 28 '15 at 17:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.